2020
DOI: 10.21315/km2020.38.s1.6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gender and Status in Communication between Doctors and Patients in Malaysian Contexts

Abstract: This study investigates the ways in which gender and status of doctors and patients influence the effectiveness of communication in sustainable health development among Malaysians. In order to conduct this research, we look at the interruption patterns in doctor-patient interaction because interruption provides an opportunity for interactants to dominate the conversation which can have negative effects on the treatment and consultation process. The data consists of 480 minutes of recorded conversations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In terms of the use of the super polite form in women's language, aspects such as interruptions as well as direct and indirect language are considered as part of the feature. In regards to interruptions, findings from multiple studies seem to differ with some reporting that both men and women interrupt at almost the same frequency (Chouchane, 2016;Karakowsky et al, 2004), while others revealed that women interrupt more than men (Ariyanti et al, 2021;Zouch, 2016), and a few studies found that men interrupt at a higher frequency than women (Ghilzai, 2018;Mohajer & Endut, 2020). However, it is worth noting that men tend to interrupt women more than they interrupt other men (Chouchane, 2016;Ghilzai, 2018) and men are more successful at taking over the conversation following their interruption (Zouch, 2016).…”
Section: Gender Differences In Language Usementioning
confidence: 98%
“…In terms of the use of the super polite form in women's language, aspects such as interruptions as well as direct and indirect language are considered as part of the feature. In regards to interruptions, findings from multiple studies seem to differ with some reporting that both men and women interrupt at almost the same frequency (Chouchane, 2016;Karakowsky et al, 2004), while others revealed that women interrupt more than men (Ariyanti et al, 2021;Zouch, 2016), and a few studies found that men interrupt at a higher frequency than women (Ghilzai, 2018;Mohajer & Endut, 2020). However, it is worth noting that men tend to interrupt women more than they interrupt other men (Chouchane, 2016;Ghilzai, 2018) and men are more successful at taking over the conversation following their interruption (Zouch, 2016).…”
Section: Gender Differences In Language Usementioning
confidence: 98%
“…Another conversation analytic study explored gender and interruptions in doctor/patient interaction and found that males made more intrusive interruptions than females and that male doctors interrupted female patients intrusively more than they interrupted male patients intrusively (Mohajer and Endut 2020).…”
Section: Literature Review Gender/ing Language and Communicationmentioning
confidence: 99%